Engineered trivalent immunogen adjuvanted with a STING agonist confers protection against Trypanosoma cruzi infection - Sanchez Alberti, Andrés (2017)
The parasite Trypanosoma cruzi is the causative agent of Chagas disease, a potentially life-threatening infection that represents a major health problem in Latin America. Several characteristics of this protozoan contribute to the lack of an effective vaccine, among them: its silent invasion mechanism, T. cruzi antigen redundancy and immunodominance without protection. Taking into account these issues, we engineered Traspain, a chimeric antigen tailored to present a multivalent display of domains from key parasitic molecules, combined with stimulation of the STING pathway by c-di-AMP as a novel prophylactic strategy. This formulation proved to be effective for the priming of functional humoral responses and pathogen-speciﬁc CD8+ and CD4+ T cells, compatible with a Th1/Th17 bias. Interestingly, vaccine effectiveness assessed across the course of infection, showed a reduction in parasite load and chronic inﬂammation in different proof of concept assays. In conclusion, this approach represents a promising tool against parasitic chronic infections.